Defective triglyceride biosynthesis in CETP-deficient SW872 cells - Diane J. Greene; Lahoucine Izem; Richard E. Morton (Journal of Lipid Research, 2015)
We previously reported that reducing the expression of cholesteryl ester transfer protein (CETP) disrupts cholesterol homeostasis in SW872 cells and causes an ∼50% reduction in TG. The causes of this reduced TG content, investigated here, could not be attributed to changes in the differentiation status of CETP-deficient cells, nor was there evidence of endoplasmic reticulum (ER) stress. In short-term studies, the total flux of oleate through the TG biosynthetic pathway was not altered in CETP-deficient cells, although mRNA levels of some pathway enzymes were different. However, the conversion of diglyceride (DG) to TG was impaired. In longer-term studies, newly synthesized TG was not effectively transported to lipid droplets, yet this lipid did not accumulate in the ER, apparently due to elevated lipase activity in this organelle. DG, shown to be a novel CETP substrate, was also inefficiently transferred to lipid droplets. This may reduce TG synthesis on droplets by resident diacylglycerol acyltransferase. Overall, these data suggest that the decreased TG content of CETP-deficient cells arises from the reduced conversion of DG to TG in the ER and/or on the lipid droplet surface, and enhanced TG degradation in the ER due to its ineffective transport from this organelle.